2010
DOI: 10.1142/s0219199710003932
|View full text |Cite
|
Sign up to set email alerts
|

Bloch-Type Conjectures and an Example a Three-Fold of General Type

Abstract: The hypothetical existence of a good theory of mixed motives predicts many deep phenomena related to algebraic cycles. One of these, a generalization of Bloch's conjecture says that "small Hodge diamonds" go with "small Chow groups". Voisin's method [22] (which produces examples with small Chow groups) is analyzed carefully to widen its applicability. A threefold of general type without 1-and 2-forms is exhibited for which this extension yields Bloch's generalized conjecture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…This way the second result of [27] (quintic hypersurfaces with involutions) and the main application of [23] (3-dimensional complete intersection in weighted projective space) are reproved : in both cases we are reduced to prove the generalized Hodge conjecture for the coniveau 1 Hodge structure on their cohomology of degree 3.…”
Section: Complete Intersections With Group Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…This way the second result of [27] (quintic hypersurfaces with involutions) and the main application of [23] (3-dimensional complete intersection in weighted projective space) are reproved : in both cases we are reduced to prove the generalized Hodge conjecture for the coniveau 1 Hodge structure on their cohomology of degree 3.…”
Section: Complete Intersections With Group Actionmentioning
confidence: 99%
“…Section 3 will provide a number of other geometric applications. For example, we will show how to recover the results of [27], or [23]. We will get more generally results for many complete intersections X b endowed with the action of a finite group G. In this case, the method applies as well to the χ-invariant part of CH(X b ) where χ : G → {1, −1} is a character.…”
Section: Introductionmentioning
confidence: 97%
“…A threefold of general type with finite dimensional motive. In [39] one of the authors investigated a quasi-smooth threefold X which is a complete intersection of three degree 6 hypersurfaces in the weighted projective space P = P(2 4 , 3 3 ) and showed that A 0 (X) = Q. Let us check that this example can also be treated within the present framework.…”
Section: Moreover In This Rangementioning
confidence: 93%
“…In this way, the second result of [98] (quintic hypersurfaces with involutions) and the main application of [82] (three-dimensional complete intersections in weighted projective space) are re-proved; in both cases we are reduced to proving the generalized Hodge conjecture for the coniveau 1 Hodge structure on their cohomology of degree 3.…”
Section: Complete Intersections With Group Actionmentioning
confidence: 94%